Variations in rumen microbiota and host genome impacted feed efficiency in goat breeds - Alaa Emara Rabee; Ibrahim Abou-souliman; Ahmed I. Yousif; Mebarek Lamara; Mohamed A. El-Sherbieny; Eman Ali Elwakeel; Ahmed M. Sallam (Frontiers in Microbiology)
IntroductionImproving feed efficiency (FE) is a significant goal in animal breeding programs. Variations in FE and its relationship with rumen microbiota remain poorly understood across different goat breeds.MethodsThis study assessed the influence of the rumen microbiome and host genome on FE in 10 Shami (SH) goats and 10 Zaraibi (ZA) goats, all of which were fed the same diet. The animals were genotyped using the Illumina 65KSNP chip arrays v2, and their rumen bacteria and archaea were investigated using PCR-amplicon sequencing of the 16S rRNA gene.ResultsThe results showed that the ZA goats exhibited higher FE than the SH goats (p < 0.05) and a greater relative abundance (p < 0.05) of rumen bacterial groups that are involved in the degradation of cellulose and hemicelluloses, such as Bacteroidota and Fibrobacterota, along with genera such as Prevotella, Lachnospiraceae AC2044 group, Lachnospiraceae NK3A20 group, and Succiniclasticum, which are linked to carbohydrate and nitrogen metabolism pathways. In addition, breed differences were found to affect the proportions of milk fatty acids. The association analysis identified 26 genome windows containing several putative candidate genes, such as TMEM241, AP4S1, FTO, HYAL2, BBS2, CD52, CRYBG2, PIGV, WDTC1, EEF1A2, GBA2, FNIP1, ACSL6, STARD10, VPS26B, ACAD8, GLB1L3, NRN1L, LCAT, and SLC7A6. These genes contributed to FE traits in Egyptian goats, as they are involved in obesity, metabolism, and the transport of energy, vitamins, fatty acids, proteins, and lipids through diverse biological pathways.DiscussionThis study suggests that specific genetic markers and rumen microbial traits could be used to identify high-efficient individuals in Egyptian goat breeds, and improving breeding strategies for FE.